MERGER AS THE FULFILLMENT OF MINIMUM CAPITAL REQUIREMENTS AND FULFILLMENT OF CORE CAPITAL BPRBASED ON FINANCIAL REGULATION NO. 5/POJK.03/2015 (CASE STUDY AT PT. BPR RANGKIANG AUR DAN PT. BPR RANGKIANG DENAI) - Dodi Yuli Satria, Nasfi (Menara Ilmu, 2019)
Abstract : Research that aims to identify, study and interpret the selection of merger alternatives as a step in PT. BPR Rangkiang Aur and PT. BPR Rangkiang Denai in addressing POJK number 5 / POJK.03 / 2015. The method used in this study is a combination research method / mix methods, namely by collecting, analyzing data, interpreting findings and drawing conclusions with quantitative and qualitative methods. The merger was carried out on the condition that the two BPRs were financially sound so the authors carried out the analysis of the health of the two BPRs using CAR, NPL, LDR, ROA, ROE and BOPO financial ratios. The results of this study indicate that the merger of PT. BPR Rangkiang Aur with PT. BPR Rangkiang Denai can fulfill the provisions of POJK number 5 / POJK.03 / 2015 with the results of CAR or KPMM reaching 15.11% with the fulfillment of core capital reaching Rp. 6,836,939 thousand, which has exceeded the minimum core capital provisions. Besides that, with the merger, the vision and mission of PT. BPR Rangkiang Aur and opens opportunities to grow better. Keywords: Merger, CAR, NPL, LDR, ROA, ROE, BOPO and FinancialRegulation No. 5/POJK.03/2015